Representasi Sifat Kikir dalam Legenda Awal Mula Babakan Aso, Kabupaten Purwakarta, Jawa Barat, Indonesia - Setiawan, Janten Hidayat; Harini, Yostiani Noor Asmi; Durachman, Memen (Universitas Islam Sumatera Utara, 2025)
This study aims to reveal the representation of miserliness as depicted in the local legend